A Case of Syncope Induced in the Supine Position - Kazuo Eguchi; Akihiro Tsujita; Syoji Ono; Kazuomi Kario (International Journal of Hypertension)
We experienced a reproducible supine syncope followed by upper abdominal pain. A 66-year-old man was transferred to our hospital after an episode of syncope during sleep. He had a history of acute pancreatitis, diabetes, hypertension, and dyslipidemia, but no history of presyncopal attack. One night, his wife noticed he was snoring abnormally in bed, and he did not respond to her voice until after she tried many times to wake him. The same attack was reproduced three times in the same situation. One of the attacks was recorded under a continuous ECG and radial tonometry. In this case, a presyncopal attack and a sense of ill-feeling were provoked by the patient lying in a prolonged supine position. He was eventually diagnosed as metastatic liver tumor 5 months after the first attack. Because few cases of syncopal attack have been reported in the supine position, its underlying mechanisms deserve consideration.